Situation Awareness and Interruption Handling During Medication Administration. (August 2014) - Sitterding, Mary Cathryn; Ebright, Patricia; Broome, Marion; Patterson, Emily S.; Wuchner, Staci
Medication administration error remains a leading cause of preventable death. A gap exists in understanding attentional dynamics, such as nurse situation awareness (SA) while managing interruptions during medication administration. The aim was to describe SA during medication administration and interruption handling strategies. A cross-sectional, descriptive design was used. Cognitive task analysis (CTA) methods informed analysis of 230 interruptions. Themes were analyzed by SA level. The nature of the stimuli noticed emerged as a Level 1 theme, in contrast to themes of uncertainty, relevance, and expectations (Level 2 themes). Projected or anticipated interventions (Level 3 themes) reflected workload balance between team and patient foregrounds. The prevalence of cognitive time-sharing during the medication administration process was remarkable. Findings substantiated the importance of the concept of SA within nursing as well as the contribution of CTA in understanding the cognitive work of nursing during medication administration.